(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Nationalization of banks in 1969 was the first strike to formalize financial sector in India. Several steps were then initiated to connect the unbanked population with banks through establishment of regional rural banks and NABARD in 1976 and 1982 respectively. Even after then lakhs of people still don’t trust formal financial institutions and are dependent on informal sector. Easy and secure access of financial services is what required by the uncatered section of the economy. This work will explore the path through which usability of the financial services can be increased by the beneficiaries (customers) in a sustainable way. The path clearly defines the importance of affordability, accessibility, awareness, attitude and usage towards the financial services in augmenting the level of financial inclusion. This work will help to comprehend the more sustained path for effective and efficient catering and consumption of financial services among seeking and vulnerable section of the economy.